2015
DOI: 10.1063/1.4928739
|View full text |Cite
|
Sign up to set email alerts
|

Forced synchronization of autonomous dynamical Boolean networks

Abstract: We present the design of an autonomous time-delay Boolean network realized with readily available electronic components. Through simulations and experiments that account for the detailed nonlinear response of each circuit element, we demonstrate that a network with five Boolean nodes displays complex behavior. Furthermore, we show that the dynamics of two identical networks display near-instantaneous synchronization to a periodic state when forced by a common periodic Boolean signal. A theoretical analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…It means that the chaos should be generated consistently for a wide range of parameter values. In the ongoing literature, the reported autonomous Boolean networks only show chaos in certain ranges of the feedback delays [10,30,31,[35][36][37][38][39], as was discussed in the Introduction section. At the experimental level, those approaches incorporate an even number of logic NOT gates in the link to act as a time-delay buffer to add extra signal propagation times.…”
Section: Boolean Chaos Robust To Different Incommensurate Time-delaysmentioning
confidence: 91%
See 3 more Smart Citations
“…It means that the chaos should be generated consistently for a wide range of parameter values. In the ongoing literature, the reported autonomous Boolean networks only show chaos in certain ranges of the feedback delays [10,30,31,[35][36][37][38][39], as was discussed in the Introduction section. At the experimental level, those approaches incorporate an even number of logic NOT gates in the link to act as a time-delay buffer to add extra signal propagation times.…”
Section: Boolean Chaos Robust To Different Incommensurate Time-delaysmentioning
confidence: 91%
“…The signal propagation time from node j to node i is τ ij for i, j = a, b, c. Theorem 3. For an autonomous Boolean network given by the system of Equation 2, the orbits are always oscillating [36].…”
Section: Bco-1mentioning
confidence: 99%
See 2 more Smart Citations
“…In [31], Ghil and Mullhaupt have introduced the Boolean delay equations as an autonomous BN (ABN), and this model has then been widely applied to yeast cell cycle and electronic circuits [32]. In [33], based on the logic gates, Rivera-Durón has built an electronic realization of an ABN of five nodes with external Boolean signal that can be regarded as control input, namely autonomous Boolean control network (ABCN) (see Example 3 for reference), and the forced synchronization issue of two identical ABNs (forced by a common external signal) has been addressed. The recent work in [34] has shown that the analysis on complex dynamics in an electronic circuit is beneficial for capturing the qualitative aspects of the structure and dynamics of GRNs.…”
Section: Introductionmentioning
confidence: 99%